Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,435 questions

17,804 answers

1,438 comments

108,773 users

How do I solve an elimination problem when the one of the coeficcint's is on the other side of the equal sign?

0 votes
-3+3y=6x

-10x+6y=4
asked Dec 6, 2014 in ALGEBRA 2 by anonymous

1 Answer

0 votes

First equation  : - 3 + 3y = 6x              ----------------(1)

Second equation : - 10x + 6y = 4             ----------------(2)

(1)  ⇒   3y = 6x + 3             ----------------(3)

Multiply with 2 both sides.

2(3y) = 2(6x + 3)

6y = 12x + 6.

Substitute 6y value in Second equation.

-10x + 6y = 4   ⇒   -10x + (12x + 6) = 4

2x + 6 = 4

Add - 6 to each side.

2x + 6 - 6 = 4 - 6

2x  = - 2

Divide each side by 2.

2x/2  = - 2/2

x = - 1.

 

Substitute x = - 1 in equation (3).

3y = 6x + 3  ⇒  3y = 6(-1) + 3

3y = - 6 + 3

3y = - 3

Divide each side by 3.

3y/3 = - 3/3

y = -1.

Solution : x = -1 , y = -1.

answered Dec 6, 2014 by Shalom Scholar

Related questions

...